Rudgea agresteophila and R. hileiabaiana (Palicoureeae, Rubiaceae): two new species from eastern Bahia, Brazil - Bruniera, Carla Poleselli; Zappi, Daniela Cristina; Groppo, Milton (Phytotaxa, 2015)
This work is part of a larger ongoing study of taxonomy and systematics of Rudgea (Rubiaceae), with the recognition of two new Brazilian species, R. agresteophila and R. hileiabaiana, described and illustrated here. The new species occur in the eastern Bahia State, Brazil, which is a place of high diversity for Rudgea. Rudgea agresteophila is morphologically distinct within the genus, by the combination of thickly coriaceous leaves, flowers with long calyx-tube and fruits crowned by a persistent calyx up to 6 mm long; and is known only from the type locality, in the municipality of Jequié. Rudgea hileiabaiana is distinguished by its coriaceous leaves, up to 30 cm long and round to cordate base, broadly infundibular corolla and unexpanded calyx; and it is restricted to southern Bahia. Detailed data on distribution and habitat, phenology and conservation status of both species are presented.